A Stoic Cyber Meta-Ontology - Applying Stoicism to Modern Ontology Design. Issue 52 (2nd January 2021) - Ormrod, David
ABSTRACT: The concept of concrete and abstract entities relates to an ontological specification problem, described by Plato's Sophist concept of the Gods and Giants and their interpretation of metaphysical reality. Developing an ontology without considering the full metaphysical implications leaves conceptual gaps in the creation of events, change in states and management of thoughts, plans and deceptions. This paper seeks to resolve conceptual gaps in the field of cyberspace representation, enabling both ontological interoperability and the development of more complex artificial intelligence technologies. The beginnings of a new meta-ontology for cyberspace are proposed, based on Stoic metaphysics. A meta-ontology provides high-level construction of meaning, upon which more specific ontologies can be built. Coherence between ontologies is important because cyberspace is a contextually dependent knowledge space within the broader infosphere, with many interdependent concepts. This paper enhances the potential for ontological interoperability and transparency between users, human or machine.